Implementasi LMS Simak Darunnajah dalam Pembelajaran Bahasa Arab untuk Meningkatkan Manajemen Teknologi Informatika di Universitas Darunnajah - Annas, Imam Khairul; Abdullah, Achmad Farouq (Indo-MathEdu Intellectuals Journal, 2026)
This study examines the implementation of LMS SIMAK Darunnajah in Arabic language learning to improve information technology management competencies in the Software Engineering study program at Darunnajah University. This pesantren-based university in South Jakarta faces a unique challenge: maintaining classical Islamic learning traditions particularly Arabic, while actively developing students' digital capabilities. Using a mixed-methods approach involving 50 students and 2 lecturers during the 2025/2026 academic year, results show that LMS SIMAK Darunnajah increased Arabic learning outcomes by an average of 34.2% (from 67.3 to 78.8), with all components showing statistically significant improvement (p<0.01). IT management competency scores reached 78.5% (Good category), significantly higher than the conventional approach at 50.6%. Student satisfaction index reached 82.7%, with the highest scores on flexibility of learning time (88.4) and integration with pesantren values (85.9). The novelty of this research lies in the simultaneous integration of Arabic learning content and IT management competency through an Islamic boarding school-based LMS platform, producing an Integrated Digital Pesantren Model (IDPM) that has not been explored in previous studies